2022
DOI: 10.1039/d1fo02832d
|View full text |Cite
|
Sign up to set email alerts
|

Yeast β-1,3-glucan production by an outer membrane β-1,6-glucanase: process optimization, structural characterization and immunomodulatory activity

Abstract: The β-glucan from Saccharomyces cerevisiae is a potent adjuvant that exhibits a broad spectrum of biological activities and health benefits, and different processes have been established to prepare active β-glucan...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It was found that yeast glucan (consisting of β‐1,3/1,6‐glucans) can be used as a wall material to encapsulate curcumin and improve acute enteritis induced by sodium glucan sulfate in rats 13 . Yeast β‐1,3‐glucan also increased the expression levels of tight junction proteins (ZO‐1, occludin and claudin‐1) and modulated gut microbiota in colitis mice 14 . Cereal β‐glucan also exhibits typical health effects of insoluble fiber, such as improving intestinal health 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that yeast glucan (consisting of β‐1,3/1,6‐glucans) can be used as a wall material to encapsulate curcumin and improve acute enteritis induced by sodium glucan sulfate in rats 13 . Yeast β‐1,3‐glucan also increased the expression levels of tight junction proteins (ZO‐1, occludin and claudin‐1) and modulated gut microbiota in colitis mice 14 . Cereal β‐glucan also exhibits typical health effects of insoluble fiber, such as improving intestinal health 15 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Yeast ⊎-1,3-glucan also increased the expression levels of tight junction proteins (ZO-1, occludin and claudin-1) and modulated gut microbiota in colitis mice. 14 Cereal ⊎-glucan also exhibits typical health effects of insoluble fiber, such as improving intestinal health. 15 However, the biological function of 1,3-⊎-D-glucan (OBG) in dextran sodium sulfate (DSS)-induced acute UC has not been fully investigated, and the relationships among gut microbes, amino acids metabolism remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Oral treatment with yeast β-glucan in non-obese diabetic mice has positive changes to immune functions by increasing IL-10, IL-17, and IL-21 levels and decreasing TNF-α level, although levels of some pro-inflammatory cytokines (IL-1b and IFN-γ) were increased [ 32 ]. Meanwhile, β-glucan from S. cerevisiae ameliorated inflammation in a DSS-induced mouse model of colitis by regulating the levels of cytokines (IL-1β, IL-6, TNF-α, and IFN-γ), increasing the expression levels of tight junction proteins [ 33 ], implying that yeast culture has favorable immunomodulatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https://www.mdpi.com/article/10.3390/foods12132486/s1, Figure S1: The enzymatic preparation of MP112 from baker's yeast by β-1,6-glucanase (the red diagram) [26].…”
Section: Supplementary Materialsmentioning
confidence: 99%